MINERALOGICAL, PETROGRAPHIC AND STABLE ISOTOPIC STUDY OF ANCIENT WHITE MARBLE QUARRIES IN THESSALY, GREECE - II. CHASANBALI, TEMPI, ATRAX, TISAION MOUNTAIN - Melfos, V.; Voudouris, P.; Papadopoulou, L.; Sdrolia, S.; Helly, B. (Bulletin of the Geological Society of Greece, 2010)
The present study focuses on the identification of marble sources from four ancient quarries in Thessaly, including Atrax, Tempi, Chasanbali and Tisaion and aims in characterizing the variations of the mineralogical and petrographic features, and the stable isotope ratios (δ13C and δ18O). The results provide additional data and complete the databases presented in previous works from Kastri, Kalochorion and Gonnoi. Microscopy was employed both to evidence the geometrical relationships among the mineral constituents, with particular reference to calcite, and to detect the accessory grains. The studied marbles demonstrate various textures, whereas the maximum grain size of calcites has been used to discriminate the marbles. The geometric relationships of carbonate grains, such as the grain boundary shape, were also evaluated. According to the stable isotope compositions, most of the samples plot in the same area, although some groupings are observed.